DEVELOPMENT OF A SAFETY MANAGEMENT SYSTEM FOR DIET PRODUCTION ON THE BASIS OF HACCP PRINCIPLES IN RESTAURANT ESTABLISHMENTS - Корецька, Ірина; Масліков, Максим; Кочерга, Ярослав; Бондаренко, Олександра (SWorldJournal, 2024)
The work presents a consideration of the importance of the HACCP system and its principles in relation to the organization of dietary food production. An analysis of hazards and step-by-step control of all stages of the preparation of dietary dishes and